COMPARING HEPATITIS B SEROPROTECTION IN PAKISTANI CHILDREN AT 5 AND 6 YEARS OF AGE AFTER EXPANDED PROGRAMME ON IMMUNIZATION (EPI) VACCINATION - Qadir, Ehsan; Malik, Qudratullah; Zahid, Muhammad; Raza, Ali; Shah, Sajid Ali; Hussain, Syed Saddam (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare seroprotection of children at 5 and 6 year of age after receiving Hepatitis B vaccination according to Expanded Programme on Immunization (EPI).Study Design: Cross sectional study.Place and Duration of Study: The study was conducted in the Department of Paediatric Medicine, Pak Emirates Military Hospital, Rawalpindi, from Oct 2015 to Apr 2016.Methodology: After the approval of ethics committee, informed consent of participants was obtained. Total 85 children, both male and female, aging 5 and 6 years were included in study fulfilling inclusion criteria. 3.5 ml blood samples were obtained ensuring antiseptic precautions using disposable syringes. Samples were taken in vaccutainers, labeled with patient’s demographic information and were immediately transported to the Armed Forces Institute of Pathology (AFIP) for analysis. Hepatitis B surface antibody titers of >10 IU/ L was taken as protective and